Atividade antifúngica dos quelantes deferiprona e ácido etilenodiaminotetracético frente a Sporothrix spp. : efeito no crescimento planctônico e formação de biofilmes - Costa, Anderson da Cunha (2020)
Sporotrichosis is a subcutaneous mycosis used by dimorphic fungi belonging to the Sporothrix schenckii complex. Fungi need metals to grow, express their virulence factors and perform biological processes. The metals limitation by chelators proved to be effective in inhibiting the growth and biofilm formation of other fungi. Thus, the present study aimed to evaluate the antifungal activity of iron chelators, ethylenediaminetetraacetic acid (EDTA) and deferiprone (DFP) and their interactions with antifungal drugs, as well as their effect on the biofilm formation of species of the S. schenckii complex. Eighteen strains of Sporothrix spp. (07 S. brasiliensis, 03 S. globosa, 03 S. mexicana and 05 Sporothrix schenckii sensu stricto). The antifungal activity of EDTA and DFP was evaluated by the broth microdilution method. The effect of the combination of the chelators with the antifungal amphotericin B, itraconazole and terbinafine was evaluated by the checkerboard method. The action of chelators in the biofilm formation process of Sporothrix spp. was analyzed by violet crystal staining and XTT reduction assay. EDTA and DFP showed minimum inhibitory concentration (MIC) varying from 32 to 128 μg/ml against the filamentous form and from 16 to 64 μg/ml (EDTA) and 8 to 32 μg/ml (DFP) against the yeast form of Sporothrix spp. The chelators showed synergism with amphotericin B, itraconazole and terbinafine. Biofilms formed in the presence of iron chelators (512 μg / ml) showed a reduction (p <0.05) of 47% in biomass and 45% in metabolic activity. It is concluded that DFP and EDTA have antifungal activity against planktonic cells of Sporothrix spp. and interact synergisticallY with classic antifungals, in addition to showing inhibitory activity in the formation of biofilm of these fungi.